The dialogue between tradition and modernity: exploring creative cultural tourism design in the 'internet plus' era. (4th September 2022) - Zong, Yuanyuan; Dai, You-Yu; Wu, Tianyu; Bu, Danwei
A heterogeneous developmental model of tourism resources in modern cities would result in a lack of vitality in the local culture. Creative cultural tourism design in the 'internet plus' era is an important issue in the development of cultural tourism integrated with creative elements. Taking Hankou historic blocks as an example, the researchers conducted a qualitative study using a combination of the volunteer-employed photo method and photo-elicitation interview to explore the framework of the experiencescape for displaying creative cultural tourism design. The results reveal four categories of experiencescapes (i.e., cultural, functional, technological, and servicescape) associated with design elements. Six tourist emotions evoked from visiting these experiencescapes and their respective elements were also categorised. The findings contribute to exploring creative cultural products at the historic block level and offer marketing implications for (re)designing more effective projects from a tourism perspective.